Syntagmatic Prototypes and Their Relevance for Semantic Fields - Žic Fuchs, Milena (1993)
The notion of prototype has become widely used in semantics during the last decade. Its importance and relevance has been shown in the analysis of individual lexemes, as well as in the analysis of semantically related lexeme, or loosely speaking "semantic fields", seen as dynamic, flexible structures on the paradigmatic level. The aim of this paper is to show that the notion of prototype can be productively extended to syntagmatic relations, more specifically, to the "more or less" typical syntagmatic environments in which we find certain verbs of motion and verbs of having in English. By combining semantic feature analysis with the analysis of typical nuclear grammatical relations found in sentences containing verbs of motion and verbs of having, we can show that paradigmatic structures can be more readily identified and described by integrating semantics and syntax. In other words, typical semantic and typical syntactic features that characterize the above mentioned verbs, can be seen as a firmer starting point or basis for detecting principles of vocabulary organization. What is more, such an approach sheds additional light on how verbs interact with lexemes on the syntagmatic level and with semantically related lexemes on the paradigmatical level, showing thus through their mutual interaction, that the notion of prototype can be seen as a link that connects syntagmatic relations and paradigmatic "semantic fields".
Projekt MZOS
ENG